Collaborative Governance Dalam Pengelolaan Hutan Mangrove: (Studi Kasus Suku Akit Desa Hutan Panjang Kecamatan Rupat Kabupaten Bengkalis) - Candra, Hadi; Mardiana, Rina; Pandjaitan, Nurmala K. (Jayapangus Press, 2025)
This study discusses the implementation of collaborative governance in mangrove forest management in Hutan Panjang Village, Rupat District, Bengkalis Regency. The Akit Indigenous People are positioned as key actors alongside the Village Government and the Forest Management Unit (KPH). The Akit community possesses local wisdom in preserving mangrove forests through traditional practices such as replanting mangrove trees after harvesting. This wisdom reflects a balance between economic utilization and environmental conservation. However, the sustainability of mangrove forests faces several challenges, including environmental degradation, climate change, and government policies that often conflict with customary norms and indigenous land rights. The purpose of this research is to analyze conservation practices, patterns of collaboration among actors, and forms of community adaptation to policy changes and environmental conditions. The study employs a descriptive qualitative approach with data collected through in-depth interviews, focus group discussions (FGDs), and documentation. Informants were selected purposively, consisting of village officials, KPH representatives, and members of the Akit Indigenous People, totaling 15 participants. The findings reveal a trust gap between the community and the government due to formal regulations such as the 2018 Regional Regulation perceived as misaligned with customary practices and local livelihoods. Consequently, community participation in government programs remains low because of concerns about restricted access to natural resources. In the collaboration process, the Village Government acts as a facilitator, the KPH functions as a technical manager through rehabilitation and training programs, while the Akit community maintains ecosystem sustainability through local wisdom. This study concludes that the sustainability of mangrove management depends on the alignment of government policies with local wisdom, strengthened communication among actors, and the provision of alternative livelihoods based on community participation. The study contributes to the development of collaborative governance theory and natural resource management grounded in the local knowledge of coastal indigenous communities.